A Response Matrix Method for One-Speed Slab-Geometry Discrete Ordinates Adjoint Calculations in Source-Detector Problems. Issue 6 (18th September 2016) - Mansur, Ralph S.; Silva, Odair P.; Moura, Carlos A.; Barros, Ricardo C.
ABSTRACT: Presented here is an application of the one-speed Response Matrix (RM) method for adjoint discrete ordinates (SN ) problems in slab geometry applied to source-detector problems. The adjoint RM method is free from spatial truncation errors, as it generates numerical results for the adjoint angular fluxes in multilayer slabs that agree with the numerical values obtained from the analytical solution of the adjoint SN equations. Numerical results are given for two typical source-detector problems to illustrate the accuracy and the efficiency of the offered RM computer code.